POLA KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN AKHLAK PESERTA DIDIK - Wahyudin, Ujang (Tawazun: Jurnal Pendidikan Islam, 2018)
This study aims to determine the leadership pattern of the principal in developing Islamic morality of students. This study was conducted with a case study in one of the Integrated Islamic Schools in the City of Bogor, namely SMPIT El Ma’mur which has a school principal with a leadership pattern that is applied can be used as a reference for other Islamic Integrated Junior High Schools in developing Islamic morality of students. From the results of research conducted, the leadership pattern of the head of SMPIT El Ma’mur in Bogor City in building Islamic morals is a unique type of leader, with a combination of three types of leadership, namely: democratic, transformational and authoritarian in a low level. This study uses a qualitative descriptive approach with a case study design at SMPIT El Ma’mur. The data in this study were obtained through literature study, and field studies, observation, documentation studies, and interviews